Past, Present and Future of Olympic Legacy in Asia - Litong, Gu (Universitas Pendidikan Indonesia, 2025)
The Olympic Games have long played a pivotal role in shaping national identity, diplomacy, and socio-political narratives, particularly in Asian contexts. From Japan’s post-WWII recovery demonstrated by the 1964 Tokyo Olympics to China’s rising global influence showcased during the 2008 and 2022 Games, the Olympics have transcended sports to become a platform for political messaging and national branding. This paper examines the evolution of the Olympic legacy in Asia, focusing on the tangible and intangible impacts on infrastructure, culture, and social values. It explores the role of the Games in urban regeneration, the promotion of soft power, and the emphasis on cultural heritage. Additionally, the paper discusses the intersection of technology and Olympic legacy, particularly the use of AI and digital platforms in preserving Olympic heritage, and the growing importance of sustainability in recent Games. By analyzing the political, cultural, and technological dimensions of the Olympics, this study underscores the Games' broader significance beyond athletic competition. It also highlights challenges, such as the underutilization of Olympic venues and the preservation of intangible cultural heritage. Future research should explore how these intersections of technology, culture, and diplomacy will shape the ongoing legacy of the Olympics in Asia.